Right to Education Act: Universalisation or Entrenched Exclusion?. Issue 1 (June 2019) - Kumar, Abhay; Shukla, Sudheer Kumar; Panmei, Mary; Narayan, Vir
Abstract: Right to Education (RTE) Act is intended to provide free and compulsory elementary education to all children aged 6–14 years. This article examines key constituents of elementary education in view of the RTE Act such as current attendance rate, types of institutions, medium of instruction, neighbourhood schools, Monthly per capita expenditure on elementary education (MPCEE)and incentives during pre- and post-RTE period using National Sample Survey Organisation's 64th (2007–2008) and 71st (2014) round of unit level data. The result shows that far from the universalisation, exclusion is getting entrenched across gender, sector, and socio-religious and economic groups. Female children, children from deprived socio-religious groups, rural areas and from the bottom MPCE quintile have not only fared lower in most of the studied parameters during the pre-RTE period, but the gap from their counterpart has widened immensely during the post-RTE period. Free education has declined and monthly per capita expenditure on elementary education has increased sharply. Children are moving out of the government to private schools. The findings raise serious questions on the intention of the government to fulfil its mandate under RTE.